Cadrul legal privind protecția vieții private și semnificația ei în epoca digitalizării [Articol] - Balaban, Sergiu (CEP USM, 2022)
It is well known that, in addition to the rights of access to fair justice, given that we are in the age of digitalization, citizens also have other rights and interests that come into play when they interact with the justice system, including those related to justice. privacy and personal data. When participating in a trial, people have a reasonable expectation that this will not unduly affect their personal life and will not expose them to unnecessary public attention.
LEGAL FRAMEWORK ON THE PROTECTION OF PRIVACY AND ITS SIGNIFICANCE IN THE ERA OF DIGITALIZATION
Keywords: access to justice; digitization; personal data